Overexpression of UHRF1 promoted the proliferation of vascular smooth cells via the regulation of Geminin protein levels. Issue 2 (26th February 2019) - Chen, Xia; Zhou, You-li; Liang, Shi-yu; Shi, Yan-chuan; Lin, Shu; Shu, Mao-qin
Abstract : Geminin is an inhibitor of DNA replication licensing and cell cycle. Our previous study demonstrates that Geminin plays an important role in regulating phenotypic diversity and growth of vascular smooth cells (VSMCs). Ubiquitin-like with PHD and RING Finger domains 1 (UHRF1) is an epigenetic coordinator, whose RING domain confers intrinsic E3 ligase activity, mediating the ubiquitination of several proteins and the protein–protein interaction. Aberrant expression of UHRF1 was related to aggressiveness of multiple human malignancies, where knockdown of UHRF1 led to decreased proliferation of cancer cells. However, it is unclear whether proper UHRF1 function is involved in aberrant proliferation and phenotypic switching of VSMCs via altering Geminin protein levels. In present study, in UHRF1-overexpressing A10 cells, 3H-thymidine and 5-ethynyl-20-deoxyuridine (EdU) and CCK8 were used to examine the proliferation of VSMCs. RT-PCR and Western blot analyses were performed to investigate whether UHRF1-mediated effects were achieved by altering Geminin expression in VSMCs. RNA-seq analysis was performed to dissect related mechanisms or signaling pathways of these effects. The results of in vitro experiments suggested that UHRF1 prompted proliferation and cell cycle of VSMCs via the down-regulation of Geminin protein levels with no change in Geminin mRNA expression. Besides, PI3K-Akt signaling pathway was increased upon UHRF1 up-regulation. Our study demonstrated that overexpressing UHRF1 was involved in VSMCs proliferation through reducing inhibitory Geminin protein levels to promote cell cycle as well as activating PI3K-Akt signaling. This may provide key knowledge for the development of better strategies to prevent diseases related to VSMCs abnormal proliferation.